Cancer in adults with intellectual disability: a systematic review of prevalence and incidence - Mc Mahon, Martin; Mc Carron, Mary; Lynch, Louise; Mc Callion, Philip; Eustace-Cook, Jessica (My University, 2025)
Background: The epidemiology and pattern of cancer in people with an intellectual disability is poorly documented. Emerging evidence reports that a different profile and trajectory of cancer burden is experienced in this population. The prevalence and incidence of cancer in this group have not been systematically synthesised. This review will address a significant gap in the evidence base. Methods: The Joanna Briggs Prevalence and Incidence methodology was used to guide the conduct of this review. Reporting the review adheres to the PRISMA checklist. Observational studies reporting prevalence and incidence of cancer and cancer subtypes in adults with intellectual disability were identified through searches of Embase, MEDLINE, CINAHL, PsycINFO, Web of Science, and grey literature from database inception dates to May 2025. A modified JBI Critical Appraisal Checklist was used to assess study quality. Meta-analyses were completed using Meta-XL., with pooled estimates reported where appropriate and narrative synthesis provided for heterogeneous results. Results: Two articles reported cancer prevalence and ten reported cancer incidences. The pooled prevalence was 2% (95% CI: 1–3%). Incidence estimates varied from 1.0 to 4.7% but were from studies with different designs and follow-up periods, limiting direct comparability. Overall, findings tentatively suggest a similar to lower overall cancer prevalence and incidence to the general population, but some studies reported higher rates of ovarian, testicular and unknown primary cancers. The methodological quality of most (n = 11) studies was high. Meta-analyses showed substantial statistical heterogeneity for included incidence studies reflecting methodological and clinical differences. Conclusions: Comparisons across studies are limited by heterogeneity in definitions of intellectual disability, study settings and cancer case identification. Challenges in synthesising cancer data in this population highlight the urgent need to identify people with intellectual disabilities at a population level and in cancer registries to help develop evidence that supports policy and practice in this area. Robust evidence is needed to inform clinical decision-making and policy development as the current epidemiological evidence is currently insufficient for this purpose.
PUBLISHED
Keywords: Intellectual disability; Cancer; Prevalence; Incidence; Mortality; Systematic review; Ageing; Cancer; Epidemiology; Health outcomes; Intellectual Disability